IFC-BIM-Based Fire Information System for Enhancing Preventive Building Maintenance - Bae, Subin; Cha, Heesung; Jiang, Shaohua (Journal of Performance of Constructed Facilities, 2025)
Recently, there has been a growing demand for tall skyscrapers and interconnected underground complexes to optimize land usage, along with advancements in construction technology. However, with the rise in large-scale structures, there has been a corresponding increase in fire incidents in these buildings. Given the severe implications of fire accidents in large buildings, strategies to mitigate fire-related damage are crucial. The foremost approach to mitigating fire damage lies in proactive measures taken during the maintenance phase, focusing on inspections, and oversight of building facility elements and fire risks. However, the existing facility safety management and inspection systems lack effective organization. Hence, this study aimed to manage facility data efficiently by integrating physical building information with maintenance data using building information modeling (BIM) and industry foundation classes (IFC), a file exchange standard. An IFC-based fire information management data model was defined to identify firefighting equipment based on 3D design information, and a graphical user interface (GUI) system was developed to effectively integrate facility managers' maintenance and fire management tasks. The study holds significance because it extends beyond basic performance data and establishes a new data system encompassing fire-related information within the existing data management framework. Additionally, the proposed system demonstrated the potential to support real-time facility maintenance by building managers and enhance proactive fire response capabilities.
Keywords: Building information modeling; Building Information Modelling; Building maintenance; Construction technologies; Fire disasters; Growing demand; Information foundation class; Land usage; Model-based OPC; Underground complexes; Building information modeling (BIM); Fire disaster; Information foundation classes (IFC); Preventive maintenance